Just by design: exploring justice as a multidimensional concept in US circular economy discourse. Issue 10 (2nd November 2022) - Berry, Brieanne; Farber, Brianna; Rios, Fernanda Cruz; Haedicke, Michael A.; Chakraborty, Sujan; Lowden, Sara Sophia; Bilec, Melissa M.; Isenhour, Cindy
ABSTRACT: Circular economies are often framed as addressing a trio of problems: environmental degradation, economic stagnation, and social ills, broadly defined. Our paper centers on this last claim – that circular economies promise social benefits. There is a dearth of literature focused on the social dimensions of circular economies (Geissdoerfer, Martin, Paulo Savaget, Nancy M. P. Bocken, and Erik Jan Hultink. 2017. "The Circular Economy – A New Sustainability Paradigm?" Journal of Cleaner Production 143 (February): 757–768. doi:10.1016/j.jclepro.2016.12.048 .), and even less attention to the meaning of social justice in the context of circular economies, let alone how it might be enacted in policy and practice. Drawing on data generated from focus groups with circular economy experts and a content analysis of US-based governmental, NGO, and business literature on circular economies, we explore whether and how justice emerges in circular economy discourse. We explore the narratives that these actors use to describe justice, and the barriers they see in achieving just and inclusive circular economies. We aim to identify the ways in which social justice is defined and discussed – or not – by the actors who seem to be most actively pushing for a circular economy (CE). Our work addresses the critical need to articulate clearly what it is we mean by social justice in relation to the CE. For if the CE is to contribute to sustainable social transformations, justice must be more than a buzzword – the CE must be just by design.